Screen-printed ceramic based MEMS piezoelectric cantilever for harvesting energy - Kok, Swee Leong; Abdul Rani , Othman; Azizah Shaaban , Ahmad (Trans Tech Publications, 2014)
Screen-printing technology provides a convenient method in fabricating thick-film conductive circuits and devices in the past few decades. Conventionally, piezoelectric thick-film is printed on alumina substrate with high mechanical Q-factor and resonates at higher frequency outside the range of ambient vibration. As the piezoelectric charge generation is proportional to the mechanical stress on the material, therefore the substrate can be removed in order to lower the natural frequency of the structure. In this paper, a series of piezoelectric ceramic cantilevers were fabricated in the form of free-standing cantilever. An additional layer of ceramic was also introduced to the upper and lower electrode to prevent delamination. The issue of zero resultant stress for the sandwiched piezoelectric cantilever was solved by repeating the electrode-PZT-electrode layer to form a multilayer structure. It was found from the experiment that an electrical output power of 32 μW was generated when it operates at its resonant frequency at 403 Hz.